RESEP KEPEMIMPINAN SANG DOKTER BANDENG (Fenomenologi Gaya Kepemimpinan dr. Daniel Nugroho S. di Bandeng Juwana Grup) - Michael Laurent; Indi Djastuti (JURNAL STUDI MANAJEMEN ORGANISASI, 2013)
Bandeng Juwana Grup is one of the famous traditional food shop in Central Java, established since 1981 and currently have employs more than six hundred employees. Behind its success story, it have a unique backgroud abaout the founder and the main leader, he is come from medical faculty. Threfore, the research has a purpose to analysize and explore the approach of leadership style that had been used by dr. Daniel Nugroho Setiabudi at Bandeng Juwana Grup, moreover it would investigate the effectiveness of the leadership style according to the Indonesia’s local culture. The research uses qualitative method with the fenomemenologi approach and the main subject of the studies was the leadership style applied by dr. Daniel Nugroho Setiabudi at Bandeng Juwana Grup. The source of data would be get by purposive sampling method as the key informan namely dr. Daniel Nugroho Setiabudi and the supporting informan were his workers. Based of this research, it can be concluded that the leadership style applied by dr. Daniel Nugroho Setiabudi was servant leadership style, with the strongest factor are listening and stewardship. However the style had an unique main foundation, that was the principal of loving each others. The leadership style was also distinctive as it had a collaboration with the local Indonesia culture. Finally, the leadership style of dr. Daniel Nugroho Setiabudi rated effective Keywords : Qualitative, Leadership Style, Servant Leadership, Globe Project, The Effective Leadership, Food and Beverages.